Aku Berkarya: Studi Kasus Ketahanan Banting Pada Difabel yang Berwirausaha - Endah Septianingsih; Uly Gusniarti (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2014)
This study attempted to find out how changed hardiness on entreprenuer 's difabel. This study used a case study. Design subjects or informants in this study were three entrepreneur's difabel which is had their personal entrepreneurminimalfor 2 years. The results obtained in this study was everyone basically already had hardy personality and past experiences made them more hardy. Burden of physical andphychic were another threat on difabel. Hardiness was an aspect that can help difabel deal with internal-external conflicts anddevelop their potential for self-actualization. Keywords: Hardiness, DifabelDaksa, Wirausaha